Hydrogen‐Bond Dynamics and Energetics of Biological Water. Issue 12 (11th December 2020) - Adhikari, Aniruddha; Park, Won‐Woo; Kwon, Oh‐Hoon
Abstract: Water molecules in the immediate vicinity of biomacromolecules and biomimetic organized assemblies often exhibit a markedly distinct behavior from that of their bulk counterparts. The overall sluggish behavior of biological water substantially affects the stability and integrity of biomolecules, as well as the successful execution of various crucial water‐mediated biochemical phenomena. In this Minireview, insights are provided into the features of truncated hydrogen‐bond networks that grant biological water its unique characteristics. In particular, experimental results and theoretical investigations, based on chemical kinetics, are presented that have shed light on the dynamics and energetics governing such characteristics. It is emphasized how such details help us to understand the energetics of biological water, an aspect relatively less explored than its dynamics. For instance, when biological water at hydrophilic or charged protein surfaces was explored, the free energy of H‐bond breakage was found to be of the order of 0.4 kcal mol −1 higher than that of bulk water. Abstract : Dynamic and energetic : Water near bio‐entities, such as proteins, are often characterized by features that make them distinct from bulk water. A brief overview is provided of some experimental and theoretical investigations that have unraveled the uniqueness of the H‐bond network underpinning the properties of such biological water, both in terms of its dynamics and energetics. Also, discussed are as to how the choice of probing techniques can dictate the scope of the information obtained and its interpretation.